2011
DOI: 10.1016/j.febslet.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Production of superoxide in chloroplast thylakoid membranes

Abstract: a b s t r a c tAccumulation of nitroxide radicals, DCP Å or TMT Å , under illumination of a thylakoid suspension containing either hydrophilic, DCP-H, or lipophilic, TMT-H, cyclic hydroxylamines that have high rate constants of the reaction with superoxide radicals, was measured using ESR. A slower accumulation of TMT Å in contrast with DCP Å accumulation was explained by re-reduction of TMT Å by the carriers of the photosynthetic electron transport chain within the membrane. Superoxide dismutase suppressed TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 20 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…The main site of O 2 •− generation is PSI. Several experiments revealed that PhQ could be the major contributor to this process (Kruk et al, 2003;Kozuleva et al, 2011Kozuleva et al, , 2014 •− appearance within the thylakoid membrane (Kozuleva et al, 2011); however, a significant part of O 2 •− formed by PhQ •− still likely diffuses outside the membrane. Nevertheless, the increasing irradiance resulted in both a larger O 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main site of O 2 •− generation is PSI. Several experiments revealed that PhQ could be the major contributor to this process (Kruk et al, 2003;Kozuleva et al, 2011Kozuleva et al, , 2014 •− appearance within the thylakoid membrane (Kozuleva et al, 2011); however, a significant part of O 2 •− formed by PhQ •− still likely diffuses outside the membrane. Nevertheless, the increasing irradiance resulted in both a larger O 2…”
Section: Discussionmentioning
confidence: 99%
“…•− , which can be detected outside the membrane when diffused there or can be detected within the thylakoid membranes (Kozuleva et al, 2011). The value of E m (O 2/ O 2 •− ) in water is −160 mV, while in hydrophobic zones of proteins and membranes it is more negative, approximately −550 mV (Wardman, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that O2 •− production within the thylakoid membranes most likely occurs via autooxidation of the membrane-bound primary electron acceptors in PSI, possibly 4Fe-4S clusters (FX, FA, and FB) [152]. The Em of FA/FA − and FB/FB − and [145,[268][269][270][271]; (C) possible means of ROS formation in PSI [152,266,[272][273][274][275]. PC is plastocyanin; P700 is a dimer of Chl a molecules, the primary electron donor; A 0A and A 0B are Chl a molecules located in branches A and B, respectively, both act as primary electron acceptors; A 1A and A 1B are phylloquinone molecules located in branch A and B, respectively, both acting as electron acceptors; F X , a 4Fe-4S cluster, a secondary electron acceptor; F A and F B , 4Fe-4S clusters, terminal electron acceptors.…”
Section: Formation Of Reduced Forms Of Oxygenmentioning
confidence: 99%
“…There, superoxide is rapidly dismutated to the more stable hydrogen peroxide by superoxide dismutase (SOD) [28]. If superoxide is produced within the thylakoid membrane [48] where SOD is absent, hydrogen peroxide can be produced by the reduction of superoxide by plastohydroquinone PQH 2 [47,49], and the same pathway also occurs within mitochondrial membrane [50]. …”
Section: Introductionmentioning
confidence: 99%